REVISITING THE LEGACY OF M. N. SRINIVAS (International Journal of Food and Nutritional Sciences, 2022)
As far as "modern" India was concerned, M. N. Srinivas was an outspoken supporter of the idea that caste was irrelevant. By embracing western ideas with Sanskrit culture, "social change in modern India" might be ushered in. During the 1960s, he proposed the idea of a "dominant caste" where the term "caste" was used informally rather than in context. The "dominant caste" has six characteristics according to Srinivas. I a large quantity of fertile land in the area, (ii) a large population, (iii) a high social status in the community, (iv) access to Western education, (v) administrative positions, and (vi) urban revenue streams. Without being overtly didactic, this was a subtle method of introducing class. Furthermore, Srinivas stated in his final public talk on "An Obituary on Caste as a System" at the National Institute of Advanced Studies that lifestyle may become more significant in social interactions, particularly in cities. In light of this, it is easy to see how Srinivas approached a class position over time, especially in regard to his time spent living in cities. The "malnourished underclass" was another topic Srinivas touched on. He emphasised the need for social workers and NGOs to prioritise on the nutritional and empowerment levels of girls, particularly in rural India.